Pengaruh Idol Worship terhadap Preferensi Pemilihan Pasangan pada K-Popers Wanita Dewasa Awal di Sumatera Barat - Kartika Aulia Rahmi; Zulian Fikry (Pusat riset dan Inovasi Nasional, 2025)
Before entering marriage, a person will generally choose a partner who meets their criteria. Choosing a partner is not something to be done carelessly, as this decision has a significant impact on the journey of the household and the harmony of the relationship in the future. Factors influencing partner selection can be very diverse, ranging from personal values, social environment, to the influence of developments in the times and mass media. One popular cultural phenomenon that also influences is K-Pop. For some people, a deep interest in K-Pop idols or artists can form certain standards or criteria in choosing a life partner. This study aims to determine the influence of idol worship on partner selection preferences among early adult female K-Popers in West Sumatra. The study subjects were 120 people selected using a snowball sampling technique. The study used a quantitative method, with instruments in the form of an idol worship scale and a partner selection preference scale compiled by researchers based on the dimensions of idol worship by Cheung and Yue (2018) and aspects of partner selection preferences by Townsend and Roberts (1993). The results of a simple linear regression analysis indicate that, in general, idol worship has no significant effect on partner choice preferences (sig = 0.405 > 0.05). However, when examined by dimension, attachment (sig = 0.002 < 0.05) and idealization (sig = 0.001 < 0.05) significantly influence partner choice preferences. This finding indicates that emotional aspects and idealization of idols can shape the criteria or ideal image of a desired partner, although idol worship does not have a direct effect overall.